PENGARUH STRATEGI PROMOSI DAN KUALITAS LAYANAN TERHADAP MINAT BELI SMARTPHONE DAN AKSESORIS (Studi Kasus Pada Toko Handphone Warwershop Purwodadi Kabupaten Grobogan) - Maftukh Zabaidi; Winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2023)
Background : In the era of globalization, cellular telephone shops must have the choice to act and act quickly and appropriately in facing competition in a business climate that is very unique and full of vulnerabilities. Promotions leverage this limited-time technique to attract buyers' interest in purchasing and using the advertised goods or services. Apart from attracting buyers' interest, the right special method makes the product or service offered ready to compete with companies in its field. The size of the service is seen from the quality of service in government associations, organizations, etc, service quality is an important number that determines the achievement of the goals of an association or organization. There are factors that influence the disposition of choice towards repurchase intention, in particular the repurchase intention is influenced by initial use, individual judgment and the client's previous purchasing experience Purpose: Based on the background and research gap above, a study is proposed with the aim of analyzing the influence of promotional strategies on consumer buying interest in Mobile Warwershop Purwodadi, analyzing the influence of service quality on consumer buying interest in Mobile Warwershop Purwodadi, analyzing the influence of promotional strategies and simultaneous service quality on, Consumer buying interest in Mobile Warwershop Purwodadi. So this research takes the title "The influence of promotional strategies and service quality on interest in buying smartphones and accessories at the Warwershop Purwodadi cellphone shop, Grobogan district.". Methods: This research uses a quantitative exploratory approach. Determining the sample size used simple random sampling and obtained a sample of 100 respondents. Analyzed using IBM SPSS Statistics Version 25 Forwindows statistical analysis techniques. Conclusion: Promotional strategies and service quality play an important role in increasing consumer buying interest Suggestion: Researchers only examine the variables Promotion Strategy, Service Quality and Buyer Interest, it is hoped that future researchers can conduct research with other variables Keywords: Promotion Strategy, Service Quality, and Consumer Purchase Interest